2017
DOI: 10.4330/wjc.v9.i3.230
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal atrial fibrillation ablation: Achieving permanent pulmonary vein isolation by point-by-point radiofrequency lesions

Abstract: Pulmonary vein isolation by point-by-point radiofrequency catheter ablation constitutes the cornerstone of catheter ablation strategies for the treatment of atrial fibrillation. However, despite advances in pulmonary vein isolation ablation strategies, long-term success rates after ablation remain suboptimal, which highlights the need to develop techniques to achieve more durable lesions. Strategies proposed to improve the durability of pulmonary vein isolation can be divided into two groups: Those addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Permanent PVI and freedom from AF recurrence are contingent upon efficient and durable RF lesion formation 22,23 . The amount of RF energy delivered to the tissue during ablation plays a central role in lesion durability 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Permanent PVI and freedom from AF recurrence are contingent upon efficient and durable RF lesion formation 22,23 . The amount of RF energy delivered to the tissue during ablation plays a central role in lesion durability 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Use of steerable sheaths has improved procedural outcomes in comparison to conventional sheaths due to the ease of manipulation, access and contact with target sites 14,19 . The rigid make up of steerable sheaths, also, reduces the effects of cardiac and respiratory excursions and provide better catheter control 23 . Several steerable sheaths are commercially available but their relative influence on CF and catheter stability remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that these two methods may have different mechanisms for the recovery of latent conduction between PV and LA. Pedrote et al 15 suggested that adenosine provocation test + pacing capture + supplemental ablation may help reduce the recurrence of AF.…”
Section: Dovepressmentioning
confidence: 99%
“…Wakili et al [14] show that contact force > 10 g can create more effective lesions. Pedrote et al [15] suggest that excessive contact force (> 50 g) can provoke steam pop. Thiagalingam et al [16] indicate that a "moderate" catheter contact force (20 g) can increase the possibility of more effective lesions, and a "high" contact force of 60 g can cause steam pop.…”
Section: Related Workmentioning
confidence: 99%